The Last Argentine Dictatorship as a School Content in Forty Years of Democracy - González, María Paula (Hispania Nova, 2026)
The teaching of the last dictatorship has been one of the strongest challenges facing the Argentine education system. And if at some point that historical process appeared unquestionably interpreted as a stage in which “state terrorism” was deployed, a closer exploration of the past reveals some tensions while a look to the future shows renewed challenges. Focusing on the secondary level, and through the differentiation of successive stages marked by political, judicial and memorial movements, the paper will show that this school question had a direction marked by the State -with lights and shadows- but also had various appropriations by institutions and teachers.
Keywords: dictatorship; education; history; secondary school; democracy